(untitled) (Caring: Indonesian Journal of Nursing Science, 2023)
Diabetes Mellitus (DM) and its complications pose a serious public health problem if not treated properly, notably diabetic ulcers, as they require a substantial amount of money and long-term treatment, sometimes up to 15 to 20 times, making amputation more likely. Approximately 14% to 24% of diabetic ulcer patients end up requiring amputation, with statistics revealing that every 30 seconds, someone loses their lower extremities due to diabetes-related diabetic ulcers. The aim of this study was to examine the relationship between family support and the quality of life in diabetic ulcer patients. The research methodology employed a cross-sectional approach using descriptive quantitative methods. Total sampling was utilized since the population was less than 100, with only 24 respondents selected for this study. The results indicated no significant relationship between family support and the quality of life, with a p-value of 0.292 (P> 0.05). Based on the results discussed in this study, it can be concluded that there is no significant relationship between family support and the quality of life in diabetic ulcer patients, as indicated by the p-value analysis result of 0.292 > 0.05. Â